Serological and molecular detection of dengue virus in animals: A systematic review and meta-analysis - Bonilla-Aldana, D. Katterine (2024)
Introduction: Dengue is a vector-borne disease, especially important in tropical and subtropical areas. The first presentation of many arboviral diseases occurred mainly in animals, including multiple Alphaviruses and Flaviviruses, such as dengue. Objective: To determine the serological and molecular frequency of the dengue virus in animals. Methods: A systematic literature review was carried out in five databases for the proportion of animals infected with dengue, defined by molecular and serological tests. A meta-analysis was performed using a randomeffects model to calculate the pooled prevalence and 95% confidence intervals (CI). Cochran?s Q test and the I2 statistic were used to assess the heterogeneity between the two studies. Results: The presence of dengue in bats, primates, birds, sheep, horses, cattle, pigs, rodents and buffaloes, according to serological methods, had a prevalence of 10%, 29%, 8%, 1%, 11%, 0%, 49%, 2%, 7%, respectively. According to molecular methods, the presence of dengue in bats had a seroprevalence of 6.0%. Conclusion: The present study confirms the presence of the Dengue virus in a large group of animal species, with potential implications as possible reservoirs of this virus, raising the possibility of zoonotic transmission.